Mucous Extractor for Tumor Tissue Sampling in Neurosurgery - Ruparelia, Jigish; Gosal, Jaskaran Singh; Garg, Mayank; Jha, Deepak Kumar; Kaur, Manbir; Kumari, Kamlesh (Asian Journal of Neurosurgery, 2023)
Objective Collection of sample for histopathological analysis is highly important during any surgical procedure. The histopathology report helps determine the diagnosis, prognosis further management, and follow-up plan. The use of a reliable sample collection technique is doubly important in neurosurgical procedures because lesions are often deep-seated and difficult to access.Materials and Methods Conventional techniques of sample collection, such as use of tumor-grasping forceps and collection of material from the ultrasonic aspirator device suffer from limitations of access and unreliability. We propose a novel technique of sample collection using readily available mucous aspirator device.Results This device is economical, sterile, and disposable. It can be used even in low-resource settings because it is easily available. It can also be connected to suction cannula and the negative pressure settings can be adjusted as required.Conclusion The use of this device for neurosurgical procedures has been tried in the transcranial and transnasal neurosurgical procedures and found to be effective. The sample collected in the canister of the mucous aspirator can be directly sent to the laboratory for histopathological analysis.
Keywords: biopsy; neuro-oncology; histopathological analysis; mucous aspirator